STRATEGI PENGAJARAN GURU DALAM MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS IV SD N NIRMALA - Farida Salsabila; Heru Purnomo (STKIP Subang, 2023)
Literacy is an important thing in students’ education in school this purpose of this research is to know strategies from teachers to improve the ability of the student to read will be held in SDN Nirmala targeting teachers and students in the fourth class. Qualitative research is showed teachers can improve their reading ability using the strategy and the correct method. Using the strategy of directed reading thinking activity (DRTA) applied by the fourth class teacher with the learning project model, the learning project model can improve the ability of proportion students to read. The obstacle factor in the process of student learning is generally located in the student’s characteristics and the student’s background does not support this since covid 19 pandemic along with learning loss in active learning.